Busca de práticas pedagógicas de professores do ensino médio: racismo e intolerância na escola - Martins, Debora Andrade Chagas (Universidade Federal de São Carlos, 2021)
This paper has the objective of looking into the development of pedagogical practices aimed at ethnic-racial education, racism overcoming and ethnic-racial differences valuing at school through documents and teachers’ testimonies. Firstly its specific objective is to analyze, from teachers’ perspective, whether Centro de Mídias São Paulo (CMSPP) has developed practices that address the ethnic-racial theme and if these practices are appropriate. Secondly, it seeks to verify whether the teachers had access to initial and/or continuing education focused on the ethnic-racial theme and the relationship between this access and the development of pedagogical practices. At last, the impacts on learning in the developed practices have been analyzed through teachers' testimonies. For this purpose, 12 high school teachers who work at a peripheral state school in Jahu, São Paulo countryside, took part. Those analyzes were carried out from theoretical references such as Franz Fanon (2008) and (2015), Kabenguele Munanga (1986) and (2004) and Nilma Lino Gomes (2012), as well as some documents. Law 10.639/03 and Opinion CNE/CP 003/04, that structure the initial theoretical basis of the research in the search for an understanding of racism, from its origin to the present day, reaching the school environment. Therefore, participatory research was adopted as methodology, characterized by a qualitative approach of a descriptive, exploratory and explanatory nature, pinpointing the data compilation process through a questionnaire and a partially structured interview. The achieved results indicate that CMSP has fulfilled properly its role regarded to the development of the topic, meaning that a great amount of teachers had access to ethnic-racial themes, whether in initial training and/or continuing education, however, these are still insufficient as development of pedagogical practices that address these themes and, finally, the practices developed by the teachers were significant to the students.
Search for pedagogical practices by secondary school teachers: racism and intolerance at school
Keywords: Ensino médio; Educação étnico-racial; Depoimento de Professores; Práticas pedagógicas; High school; Ethnic-racial education; Teachers’ testimonials; Pedagogical practices; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM